2013
DOI: 10.3892/or.2013.2663
|View full text |Cite
|
Sign up to set email alerts
|

Co-transduction of ribosomal protein L23 enhances the therapeutic efficacy of adenoviral-mediated p53 gene transfer in human gastric cancer

Abstract: Induction of murine double minute 2 (MDM2) expression is thought to be a determinant of resistance to p53 gene therapy for cancer. Previous studies have revealed that ribosomal protein L23 (RPL23) inhibits MDM2-mediated p53 degradation through direct binding to MDM2. In addition, ectopically expressed RPL23 was reported to interact with MDM2 in both the nucleus and cytoplasm, by which RPL23 indirectly inhibited MDM2-p53 binding. Based on the known molecular properties of the RPL23 protein, it was speculated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 28 publications
1
20
0
Order By: Relevance
“…7C). This finding was consistent with previous reports (Meng et al, 2016;Zhang et al, 2010Zhang et al, , 2013. Interestingly, RPL23-mediated growth suppression was restored by co-expression of GRWD1 (Fig.…”
Section: Grwd1 Modulates Mdm2 Protein Levels By Regulating Rpl23supporting
confidence: 94%
See 2 more Smart Citations
“…7C). This finding was consistent with previous reports (Meng et al, 2016;Zhang et al, 2010Zhang et al, , 2013. Interestingly, RPL23-mediated growth suppression was restored by co-expression of GRWD1 (Fig.…”
Section: Grwd1 Modulates Mdm2 Protein Levels By Regulating Rpl23supporting
confidence: 94%
“…In addition, RPL23 inhibits MDM2 ubiquitin ligase activity. Therefore, RPL23 may act as a tumor suppressor Jin et al, 2004;Meng et al, 2016;Zhang et al, 2010Zhang et al, , 2013. By contrast, our previous study identified GRWD1 as a novel negative regulator of p53 and a potential oncogene .…”
Section: Grwd1 Modulates Mdm2 Protein Levels By Regulating Rpl23mentioning
confidence: 57%
See 1 more Smart Citation
“…Adenovirus Ad5 dsDNA Strong immunogenicity Broad host range [37,38] Brain [39] Colon [40,41] Esophaegal [42] Gastric [43] Liver [44] Lung [45] Adeno associated viruses AAV (2,3,5,6,8,9) ssDNA Slow expression onset Chromosomal integration [46][47][48][49] Brain [50] Breast [51] Liver [52,53] Lung [54] Prostate [55] Retinoblastoma [56] Alphaviruses SFV, SIN ssRNA Broad host range low immunogenicity [32] Brain [57] Colon [58] Lung [59] Melanoma [60,61] Osteosarcoma [62] Pancreas [63] Prostate [64] Herpes simplex virus HSV1, HSV dsDNA Broad host range Latent infection [65,66] Brain [67,68] Colon [69] Prostate [70] Sarcoma [71] Skin [72] Reoviruses [76,79,80] Breast [81] Gastric ...…”
Section: Genome Characteristics Cancer Typesmentioning
confidence: 99%
“…It remains to be investigated whether cellular senescence might be involved in the potential mechanisms resulting in RPL23 overexpression MDS patients or is a subordinate aspect. Interestingly, RPL23 has been reported to functionally inhibit the HDM2 ubiquitin ligase and thereby activate p53, leading to growth inhibition and anti-tumour effects in cases of gastric cancer [27][28][29] . In our RPL23-KD SKM-1 cells, however, decreased RPL23 expression was correlated with the induction of apoptosis, and our western Fig.…”
Section: Ink4bmentioning
confidence: 99%